2013
DOI: 10.3109/13880209.2013.816860
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect ofBasella albaandCarpolobia albaextracts against maneb-induced male infertility

Abstract: Context: Male infertility is one of the leading causes of social frustration and marginalization, mainly in the developing world. It is attributed to many factors including exposure to agropesticides such as manganese ethylenebis (dithiocarbamate) (maneb), which is one of the most frequently used fungicides in Cameroon. Previous reports support efficiency of some medicinal plants commonly used in Cameroonian folk medicine for the treatment of this disorder. Objective: The present study was aimed at assessing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…30 Indeed, MEBa dissolved in 2% SS could protect male rats against pesticide (maneb) - induced reproductive toxicity. 7 This antioxidant potential of MEBa when dissolved in 2% SS brings further justification of the beneficial effects of starch as solubilizer compared to polyvinylpyrrolidone and other polymers, including gelatin. Indeed, the use of gelatin as vehicle for MEBa administration also led to increased liver TBARS, which are products resulting from membrane lipids degradation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…30 Indeed, MEBa dissolved in 2% SS could protect male rats against pesticide (maneb) - induced reproductive toxicity. 7 This antioxidant potential of MEBa when dissolved in 2% SS brings further justification of the beneficial effects of starch as solubilizer compared to polyvinylpyrrolidone and other polymers, including gelatin. Indeed, the use of gelatin as vehicle for MEBa administration also led to increased liver TBARS, which are products resulting from membrane lipids degradation.…”
Section: Discussionmentioning
confidence: 96%
“…The androgenic effect of the MEBa dissolved in 2% SS was previously reported, and the current findings further emphasize on its ability to preserve activity of the bioactive ingredient(s) from the extract. 3,6,7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Chen, Hardy, and Zirkin () concluded that the inability of aged rat Leydig cells (from 21 to 24 month old rats) to produce testosterone in the presence of LH in vitro was possibly due to inefficient signal transduction during steroidogenesis. Other plants such as Eurycoma longifolia , Hibiscus macranthus and Basella alba are also reported to boost testosterone levels, thus exhibiting aphrodisiac properties and increasing sexual motivation and performance (Manfo et al., ; Moundipa et al., ; Solomon, Erasmus, & Henkel, ; Tambi, Imran, & Henkel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to pesticides produces numerous biochemical and physiological alterations in human and their population in the agriculture fields [2,3]. Many pesticides are capable to disrupt the synthesis of sex hormones, which can cause reproductive disorders such agrochemicals have been documented as endocrine disrupting chemicals EDCs [4]. The farmers/spray workers are directly exposed to pesticides through occupational activities and spraying pesticides on crops.…”
Section: Introductionmentioning
confidence: 99%